Implementation of an Educational Meteorological System Using IoT and Rasperry PI - Santillán Carranza, Holger Jorge; Wong Wong, Peregrina; Romero Alvarado, Kevin Ezequiel; Huayamave Cordero, María José (INGENIO, 2024)
The subsequent document presents an examination and inquiry into a weather system utilizing IoT technology and Raspberry Pi. The primary aim is to illustrate one of the numerous applications of emerging technologies. A compact WLAN network is established to link the server of the weather station to a home automation controller through a Raspberry Pi device. This enables the incorporation of the Internet of Things into the envisioned system and the gathering of data from various sensors within the weather station. Furthermore, these data are compared with those obtained by other online systems over a specific timeframe, affirming the sensors' efficiency with a precision rate of 97.66% and the accuracy of the collected data. This creates a precedent for future research in the realms of home automation and telecommunications.